Applying design thinking for business model innovation - Xinya You (Journal of Innovation and Entrepreneurship, 2022)
In recent years, there has been an increasing interest in using design thinking for business model innovation. However, few studies have explored the application, potential and challenges of design thinking from a comprehensive perspective. In order to better understand how design thinking can contribute to business model innovation, this paper regards business model innovation as a subject of design research and provides a critical review of researchers' explorations of how to apply design thinking for business model innovation. In light of the literature review, this paper distils seven key design research themes: (1) design thinking as a mindset and a methodology; (2) designers of business models; (3) design activities for business model innovation; (4) design tools for business model innovation; (5) design approaches for business model innovation; (6) co-creation of new products, services and business models, and (7) evaluating and measuring the impact of design thinking. The themes not only highlight the potential of applying design thinking as a necessary mindset and methodology to business model innovation, but also emphasise the nature of designing as a social process.
Keywords: 650; Business model innovation; Design methodology; Design processes; Design thinking; Mindset